LEXICAL DISTORTION: A STUDY ON INDONESIAN-ENGLISH TRANSLATION - Ramli Ramli (Universitas Islam Negeri Alauddin Makassar, 2019)
Lexicon plays a fundamental role in translation. A good and acceptable translation should successfully render the message of source language into target language by selecting appropriate lexicon. The incorrectly lexical choice will distort the message of the source language. This paper investigates the lexical errors found in the translation of Indonesian text into English text made by the fifth-semester students. The data collection was conducted by administering a translation test to the respondents of 30 students. The data were analyzed using error analysis method following 5 steps: elicitation, registering, identifying, categorizing, and evaluating. The analysis and interpretation found that the lexical distortions can be categorized into: omission, overinclusion, misselection, disordering, and blending. Misselection is found to be the most dominant error followed respectively by omission, misordering, overinclusion, and blending. The findings show that the main problem of the translation is the wrong selection of lexicon and can contribute to the evaluation teaching-learning process either theoretically or practically. As a result, the improvement of students’ translation quality requires students to practice more and more. In addition, the teaching of translation should be focused primarily on the selection of lexicon.